2008
DOI: 10.1111/j.1365-2850.2008.01317.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of physical exercises to mental state and quality of life in patients with schizophrenia

Abstract: The purpose of this study was to examine the effects of 10 weeks of physical exercises programme on mental states and quality of life (QOL) of individuals with schizophrenia. The study involved 30 inpatients or outpatients with schizophrenia who were assigned randomly into aerobic exercise (n = 15) group and control (n = 15) group, participated to the study voluntarily. There were no personal differences such as age, gender, disorder duration, medication use between the both groups. An aerobic exercise program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
100
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(121 citation statements)
references
References 28 publications
9
100
0
8
Order By: Relevance
“…19 studies utilised SRQs Archie et al, 2007Arbour, Faulkner, & Cohn, 2010;Brown, Birtwistle, Roe, & Thompson, 1999, Brown, Goetz, Van Sciver, Sullivan, & Hamera, 2006Dubbert et al, 2006;Ellingrod et al, 2011;Elmslie, Mann, Silverstone, Williams, & Romans, 2001;Faulkner et al, 2006;Lassenigus, kerlind, Wiklund-Gustin, Arman, & Söderlund, 2013;Lindamer et al, 2008;McLeod, Jaques, & Deane, 2009;Osborn, Nazareth, & King, 2007;Ratliff et al, 2012;Ussher, 2003;Ussher, Doshi, Sampuran, & West, 2011;Van Citters et al, 2010;Vancampfort, Probst, Knapen, Carraro, & De Hert, 2012. Excluded studies (with reason) 55 did not use an outcome measure that provided an assessment of the three fundamental domains of physical activity Acil, Dogan, & Dogan, 2008;Adams, 1995;Aquila, 2000;Archie, Wilson, Osborne, Hobbs, & McNiven, 2003;Ball, Coons, & Buchanan, 2001;Barton, Griffin, & Pretty, 2012;Beebe et al, 2005;Bobes et al, 2010a,b, Bobes, Arango, Garcia-Garcia, & Rejas, 2010bBrill et al, 2007;Brunero & Lamont, 2010;Buhagiar, Parsonage, & Osborn, 2011;Centorrino et al, 2006;Charmove, 1986;Chuang, Mansell, & Pattern, 2008;Crone et al, 2004;Daumit et al, 2005;Davidson et al, 1999Davidson et al, , 2001…”
Section: The Identification Of the Different Outcome Measures Usedmentioning
confidence: 99%
“…19 studies utilised SRQs Archie et al, 2007Arbour, Faulkner, & Cohn, 2010;Brown, Birtwistle, Roe, & Thompson, 1999, Brown, Goetz, Van Sciver, Sullivan, & Hamera, 2006Dubbert et al, 2006;Ellingrod et al, 2011;Elmslie, Mann, Silverstone, Williams, & Romans, 2001;Faulkner et al, 2006;Lassenigus, kerlind, Wiklund-Gustin, Arman, & Söderlund, 2013;Lindamer et al, 2008;McLeod, Jaques, & Deane, 2009;Osborn, Nazareth, & King, 2007;Ratliff et al, 2012;Ussher, 2003;Ussher, Doshi, Sampuran, & West, 2011;Van Citters et al, 2010;Vancampfort, Probst, Knapen, Carraro, & De Hert, 2012. Excluded studies (with reason) 55 did not use an outcome measure that provided an assessment of the three fundamental domains of physical activity Acil, Dogan, & Dogan, 2008;Adams, 1995;Aquila, 2000;Archie, Wilson, Osborne, Hobbs, & McNiven, 2003;Ball, Coons, & Buchanan, 2001;Barton, Griffin, & Pretty, 2012;Beebe et al, 2005;Bobes et al, 2010a,b, Bobes, Arango, Garcia-Garcia, & Rejas, 2010bBrill et al, 2007;Brunero & Lamont, 2010;Buhagiar, Parsonage, & Osborn, 2011;Centorrino et al, 2006;Charmove, 1986;Chuang, Mansell, & Pattern, 2008;Crone et al, 2004;Daumit et al, 2005;Davidson et al, 1999Davidson et al, , 2001…”
Section: The Identification Of the Different Outcome Measures Usedmentioning
confidence: 99%
“…2,3 A recent systematic review demonstrated that patients with schizophrenia who participate less in physical activities have experience more negative symptoms, antipsychotic side effects, low selfefficacy, and other unhealthy lifestyle habits. 4 The important mental and physical benefits of exercise in patients with schizophrenia include improvement of symptoms, 5,6 a decreased need for care, 7 improved quality of life, 8 increased cardiorespiratory capacity, 9 increased muscle strength, 10 and increased functional capacity. 5 Studies of physical exercise among patients with schizophrenia have examined aerobic exercise, 6,9,11 which is characterized by repeated rhythmic movements of the large muscle groups of the body, such as those in the arms and legs.…”
Section: Introductionmentioning
confidence: 99%
“…However, the improvement in cardiopulmonary fitness attenuated changes in brain volume in schizophrenia and increased thickness over large areas of the cortex in both schizophrenia patients and healthy controls. Acyl et al [32], in a study of 30 patients with schizophrenia users of antipsychotics for an average of about 10 years, with mean age between 21-45 years, were divided into control group and experimental group, and performed a program of aerobic exercise for 10 weeks 3 days a week and 40 minutes per day. After 10 weeks of exercise of applying found a significant decrease in hallucinations and delusions of patients.…”
Section: Effects Of Exercise On Mental Health Cognition and Corticalmentioning
confidence: 99%
“…There are several types of training that can be used for promoting mental health, but the prescription forms and its effects in psychiatric patients, more specifically in schizophrenia, needs to be further studied [31]. For example, in Acyl et al [32] study the effectiveness of exercise was demonstrated, indicating that it may be a very efficient method of improving positive and negative symptoms in schizophrenia. Some studies show that effects on symptoms, cognition and brain activity as a result of exercise practice, depending exclusively on its duration, intensity, and how to conduct the exercise individually [33].…”
Section: Introductionmentioning
confidence: 99%